Primary xanthoma of the mandible - de Moraes Ramos-Perez, FM (The British Institute of Radiology., 2011)
Bone xanthomas are rare and are usually are associated with endocrine or metabolic diseases, mainly lipid disorders. In the absence of systemic diseases, the lesion is called a primary xanthoma. Primary mandibular xanthomas are extremely rare. The aim of this report is to describe the clinical and radiographic findings of a primary mandibular xanthoma, discussing the epidemiological features, pathogenesis and differential diagnosis. A 25-year-old man was referred for evaluation of a left mandibular lesion detected in a routine radiographic exam. Radiographically, there was a diffuse, unilocular and radiolucent lesion, with irregular margins located adjacent to the surface from the distal root of the left mandibular third molar. The lesion was excised under local anaesthesia. Microscopically, there were several cells with a foamy and granular cytoplasm and central small, round nuclei, similar to xanthomatous macrophages. No lipid disorders were diagnosed. According to these features, the diagnosis of primary mandibular xanthoma was established. In conclusion, xanthomas of the jaws are rare and all seem to be primary and occur exclusively in the mandible.